Sintesis Biodiesel Dari Low Grade Crude Palm Oil (LGCPO) Menggunakan Katalis Sulfonated Carbon Nanospheres@Ferromagnetic (HSO3-CNSS@Fe3O4) - Heru Kristianto; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Biodiesel is an alternative fuel that is environmentally friendly. Catalysts is commonly used in the production of biodiesel is strong base catalysts which is difficult to separate from the product because it has the same phase as the reactant. Therefore, it is necessary to develop catalyst technology that is more economical, easy to implement, and environmentally friendly, such as sulfonated carbon nanospheres@ferromagnetic catalyst. The catalyst was synthesized by reacting granulated sugar, FeCl2, FeCl3, and the addition of ammonia through a hydrothermal carbonization process for further sulfonated using 98% concentrated sulfuric acid. The catalyst produced has a nanospherical shape with a size of 0.08-0.16 μm. The catalyst is then used in the transesterification reaction to produce biodiesel. Optimum condition is reached at process variables LGCPO weight of 50 grams, stirring speed of 400 rpm, reaction time of 120 minutes, and temperature of 60 oC, with catalyst concentration of 1.5% (w/w) and molar ratio methanol:oil 1:9. The yield of biodiesel is 96.62% with density 878.67 kg/m3, viscosity 3.28 mm2/s, the acid number of 0.29 mg-KOH/g biodiesel and the flash point 127°C comply with the SNI standards (SNI 7182: 2015). Keywords: Biodiesel, carbon nanosphere, LGCPO, transesterification, yield